Phenotypic variation of the housefly, Musca domestica: amounts and patterns of wing shape asymmetry in wild populations and laboratory colonies. Issue 1 (February 2014) - Ludoški, J.; Djurakic, M.; Pastor, B.; Martínez-Sánchez, A. I.; Rojo, S.; Milankov, V.
Abstract Musca domestica L. (Diptera: Muscidae) is a vector of a range variety of pathogens infecting humans and animals. During a year, housefly experiences serial population bottlenecks resulted in reduction of genetic diversity. Population structure has also been subjected to different selection regimes created by insect control programs and pest management. Both environmental and genetic disturbances can affect developmental stability, which is often reflected in morphological traits as asymmetry. Since developmental stability is of great adaptive importance, the aim of this study was to examine fluctuating asymmetry (FA), as a measure of developmental instability, in both wild populations and laboratory colonies of M. domestica. The amount and pattern of wing shape FA was compared among samples within each of two groups (laboratory and wild) and between groups. Firstly, the amount of FA does not differ significantly among samples within the group and neither does it differ between groups. Regarding the mean shape of FA, contrary to non-significant difference within the wild population group and among some colonies, the significant difference between groups was found. These results suggest that the laboratory colonies and wild samples differ in buffering mechanisms to perturbations during development. Hence, inbreeding and stochastic processes, mechanisms dominating in the laboratory-bred samples contributed to significant changes in FA of wing shape. Secondly, general patterns of left–right displacements of landmarks across both studied sample groups are consistent. Observed consistent direction of FA implies high degrees of wing integration. Thus, our findings shed light on developmental buffering processes important for population persistence in the environmental change and genetic stress influence on M. domestica.